2017
DOI: 10.1002/dvdy.24560
|View full text |Cite
|
Sign up to set email alerts
|

Rebooting the collagen gel: Artificial hydrogels for the study of epithelial mesenchymal transformation

Abstract: The collagen gel has been used to study epithelial-mesenchymal transformation (EMT) for over 30 years. With advances in the field of materials sciences, new options are available to design optically clear, three-dimensional nature-inspired matrix mimetics to study EMT. Here, we review the history of the collagen gel assay, discuss its current use and how newer artificial matrices can be built to simulate in vivo extracellular environments and investigate important current questions in the EMT field. We suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The interstitial Col-I fibril lattices function as both a cell scaffold and a barrier to prevent cell migration in cancer invasion process (6,66). Furthermore, EMT induction via adhesion to Col-I is thought to enhance cancer invasion (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interstitial Col-I fibril lattices function as both a cell scaffold and a barrier to prevent cell migration in cancer invasion process (6,66). Furthermore, EMT induction via adhesion to Col-I is thought to enhance cancer invasion (32).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo, many kinds of cells are found resting proliferation within Col-I fibrils containing matrix, while, cellextracellular matrix (ECM) interactions are essential for cell movement (1). For a long while, Col-I has been widely studied and used as a cell culture substrate (1)(2)(3)(4)(5)(6)(7). Typically, Col-I is solubilized under acidic conditions and extracted from animal tissues.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMT refers to the phenomenon of epithelial cells transforming into mesenchymal cells under specific physiological and pathological conditions ( 21 , 22 ). Cells may lose their connection and polarity, change in morphology, and their migration ability may be enhanced, thus gaining invasion and metastasis abilities ( 23 , 24 ). It has been reported that although melanocytes are not traditional epithelial components, there is EMT in the process of melanoma invading dermal stroma ( 25 ).…”
Section: Introductionmentioning
confidence: 99%